2020
DOI: 10.1016/j.hrthm.2020.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of arrhythmias and electrocardiographic abnormalities in symptomatic pediatric patients with PCR-positive SARS-CoV-2 infection, including drug-induced changes in the corrected QT interval

Abstract: BACKGROUND There is limited data regarding the electrophysiological abnormalities and arrhythmias in children with COVID-19, including those associated with treatment using potentially proarrhythmic hydroxychloroquine (HCQ) and azithromycin (AZN).OBJECTIVES To describe the electrophysiologic findings and arrhythmias associated with pediatric COVID-19 and its treatment.METHODS A single-center retrospective chart review was undertaken and included all patients with (1) symptoms of COVID-19 and (2) PCR-positive n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 17 publications
0
51
0
1
Order By: Relevance
“…We had anticipated a limited overlap with findings in children and adult patients presenting with polymerase chain reaction-positive COVID-19 where arrhythmias had been seen in up to 16.7% of patients, but of particular concern in those with pre-existing cardiovascular morbidity. 20 , 21 , 22 , 23 We therefore undertook a systematic analysis of ECGs in this novel disease to focus on findings previously described in children affected by myopericarditis and Kawasaki disease. Indeed, with the exception of high-grade AV block, we showed significant overlap with these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…We had anticipated a limited overlap with findings in children and adult patients presenting with polymerase chain reaction-positive COVID-19 where arrhythmias had been seen in up to 16.7% of patients, but of particular concern in those with pre-existing cardiovascular morbidity. 20 , 21 , 22 , 23 We therefore undertook a systematic analysis of ECGs in this novel disease to focus on findings previously described in children affected by myopericarditis and Kawasaki disease. Indeed, with the exception of high-grade AV block, we showed significant overlap with these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, proarrhythmic effects of these drugs cannot be excluded in this cohort. Previous reports point towards significant prolongation of the QTc interval by hydroxychloroquine in COVID-19 which is even more enhanced in combination with azithromycin therapy [ 25 , 26 ]. However, the rate of associated ventricular arrhythmia has been low in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The data are even more limited regarding the electrophysiological abnormalities and arrhythmias in children with COVID-19 [ 89 , 90 ]. A recent study of 36 pediatric patients reported that significant arrhythmias were infrequent (albeit, more common than expected in a general pediatric population), observed in 6 children (NSVT in 5 and sustained atrial tachycardia in 1), all self-resolving; prophylactic antiarrhythmic therapy was employed in half [91] . Patients with significant arrhythmias were likely to have noncardiac comorbidities (4/6), but these were not more common than in patients without arrhythmias (20/30, p =1).…”
Section: Current Literature Limitations and Future Directionsmentioning
confidence: 96%